Peningkatan Motivasi Belajar Peserta Didik Kelas X SMA IT Izzuddin Palembang dengan Menggunakan Metode Perang Dinding Pada Materi Teks Biografi - Arindza, Anada; Lestari, Hikmah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Based on the results of observations at SMA IT Palembang in Indonesian language subjects, students tend to be sluggish and lack enthusiasm. Apart from that, there are some students who are reluctant to participate when learning activities take place. It can be concluded that students' learning motivation tends to be weak, especially in Indonesian language lessons which have a sleepy impression and lots of text, especially biographical texts. Moreover, Indonesian language subjects in class Combining games into learning that seems full of text certainly makes students curious. The use of the wall war method is expected to increase students' learning motivation and understanding of biographical text learning material. This research will examine increasing students' learning motivation on biographical text material using the wall war method. Based on the explanation and discussion above, the results obtained are that the application of learning methods, namely the games method in biographical text learning activities, is able to support increased student learning motivation. Likewise, it is able to improve self-regulation and student learning outcomes, especially wall war games.